2002
DOI: 10.1046/j.1464-410x.2002.02912.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dimethyl sulphoxide and heparin on stretch‐activated ATP release by bladder urothelial cells from patients with interstitial cystitis

Abstract: Objective To determine whether dimethyl sulphoxide (DMSO) and heparin reduce the greater stretchactivated ATP release in interstitial cystitis (IC), as ATP serves as a nocio-neurotransmitter in the bladder, and thus explain their beneficial effects in patients with IC (a disease characterized by hypersensory bladder symptoms). Materials and methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…One is that purinergic nerve-mediated contraction of the human bladder is increased to 40% in pathophysiological conditions such as interstitial cystitis, outflow obstruction, idiopathic detrusor instability, and probably also neurogenic bladder (Wammack et al, 1995;Andersson, 1997;Andersson and Hedlund, 2002). ATP release from bladder epithelial cells from patients with interstitial cystitis is significantly greater than that from healthy cells (Sun and Chai, 2002), and there is a change in expression of both P2X and P2Y receptors in urothelial cells (Birder et al, 2004;Tempest et al, 2004). P2X 1 receptor subtype expression markedly increased in obstructed bladder (Boselli et al, 2001) and in the absence of P2X 3 receptors in mouse knockouts, the bladder is hyperactive (Cockayne et al, 2000;Vlaskovska et al, 2001).…”
Section: B Lower Urinary Tractmentioning
confidence: 99%
“…One is that purinergic nerve-mediated contraction of the human bladder is increased to 40% in pathophysiological conditions such as interstitial cystitis, outflow obstruction, idiopathic detrusor instability, and probably also neurogenic bladder (Wammack et al, 1995;Andersson, 1997;Andersson and Hedlund, 2002). ATP release from bladder epithelial cells from patients with interstitial cystitis is significantly greater than that from healthy cells (Sun and Chai, 2002), and there is a change in expression of both P2X and P2Y receptors in urothelial cells (Birder et al, 2004;Tempest et al, 2004). P2X 1 receptor subtype expression markedly increased in obstructed bladder (Boselli et al, 2001) and in the absence of P2X 3 receptors in mouse knockouts, the bladder is hyperactive (Cockayne et al, 2000;Vlaskovska et al, 2001).…”
Section: B Lower Urinary Tractmentioning
confidence: 99%
“…Both resting and evoked ATP release from urothelial cells was significantly higher after chronic spinal cord injury [644]. In paraplegic patients with suprasacral lesions, the management of urinary incontinence resulting from hyperreflexic detrusor contraction is a frequent problem.…”
Section: Detrusor Overactivitymentioning
confidence: 99%
“…It was suggested that enhanced penetration of endogenous ATP due to urothelial damage may contribute to urinary frequency and bladder pain in hypersensitive bladder in BPS/ IC [524]. Urothelial cells from patients with IC released significantly more ATP in response to stretch than did control cells [644]. Further, the authors showed that the stretchactivated ATP release was blocked by adding dimethyl sulphoxide or heparin, both intravesical agents commonly used to treat the symptoms of IC.…”
Section: Detrusor Overactivitymentioning
confidence: 99%
“…P2X 3 -and P2X 3 /P2X 2 -deficient mice have problems with the micturition response, proving these findings with mouse genetics [64,65,79,83]. Chai and Sun have shown that ATP release and signaling process is heightened in interstitial cystitis (IC) [63,77]. There are also alterations in P2 receptor expression in IC [70,74].…”
Section: Tls Of Henlementioning
confidence: 99%